Evaluation of Ankle-Brachial Pressure Index and Carotid Intima Media Thickness by Doppler Ultrasound in type two Diabetics. - AL-Siaidy, Wijdan F.; AL-Sabbagh, Ahmed A.; AL-Karawi, Isam N.; Mohammed, Dalya A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Atherosclerosis causes thickening of the artery walls. The intima-media thickness (IMT) of the common carotid artery (CCA) is widely used as an early indicator of the development of coronary artery disease, atherosclerosis, and independently cardiovascular disease (CVD). Diabetes increased the risk of cardiovascular disease, also accelerates the common IMT progression. The Sonographic measurement of carotid intima-media thickness is used as a valid simple and noninvasive method for the assessment of atherosclerosis disease.Also the ankle brachial index (ABI) is considered as a strong predictor for future cardiovascular events, and a golden standard for the diagnosis of peripheral arterial disease (PAD).Objectives: To estimate the validity of carotid IMT plus the ankle brachial index as a marker of atherosclerosis in diabetic patients.Materials and methods: This study involved (101) patients with type 2 Diabetes Mellitus, (37) with hypertension and (64) without hypertension. (46) normal volunteers represent the (Control group). The three groups were subjected to the routine laboratory tests including: fasting blood sugar, lipid profile. Measurements of blood pressure, BMI, waist circumference were taken, ECG, carotid intima media thickness and ABI by using Doppler ultrasound machine.Results: Statistical significant differences are found for the mean of the carotid intima media thickness, lipid profile, and systolic blood pressure for both arms and legs in type 2 D M patients with and without hypertension, and normal subjects. The diabetic patient's data revealed an increase in the carotid IMT more than the non diabetic subjects. Furthermore no significant differences were found to exist in ABI results among the diabetic and normal groups.Conclusion: The external examination by Doppler ultrasound of the carotid intima media thickness can be used to predict the occurrence of artery atherosclerosis, while ABI is less validated in this study with the selected type 2 diabetes mellitus patients without any cardiovascular disease.